22 UMP researchers listed 2 worlds top scientists for two achievement categories - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 14 October 2022 - A total of 22 researchers from Universiti Malaysia Pahang (UMP) are listed as 2 per cent of the world’s top scientists for two achievement categories.